2009
DOI: 10.1016/j.pathophys.2009.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic fields stress living cells

Abstract: Electromagnetic fields (EMF), in both ELF (extremely low frequency) and radio frequency (RF) ranges, activate the cellular stress response, a protective mechanism that induces the expression of stress response genes, e.g., HSP70, and increased levels of stress proteins, e.g., hsp70. The 20 different stress protein families are evolutionarily conserved and act as 'chaperones' in the cell when they 'help' repair and refold damaged proteins and transport them across cell membranes. Induction of the stress respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(96 citation statements)
references
References 62 publications
3
91
0
2
Order By: Relevance
“…Once activated, the stress response induces the expression of stress response genes, such as heat shock protein 70 (HSP70), leading to an increased level of stress proteins. 4 The stress proteins act as chaperones by helping repair and refold damaged proteins and transport them across cell membranes. To induce this stress response, DNA must be activated, and despite the large energy differences between ELF and RF, they activate the same cellular pathways.…”
Section: Feature Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Once activated, the stress response induces the expression of stress response genes, such as heat shock protein 70 (HSP70), leading to an increased level of stress proteins. 4 The stress proteins act as chaperones by helping repair and refold damaged proteins and transport them across cell membranes. To induce this stress response, DNA must be activated, and despite the large energy differences between ELF and RF, they activate the same cellular pathways.…”
Section: Feature Articlementioning
confidence: 99%
“…Specific DNA sequences on the promoter of the HSP70 stress gene are responsive to EMF, and it has been suggested that EMFs could also interact directly with electrons in DNA. 4 However, EMFs with energy in the RF range can lead to breaks in the DNA strand. 4 Thus, any extensive damage or changes to DNA that need repair may increase the risk of developing cancerous cells.…”
Section: Feature Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Since melatonin is an antioxidant and its decrease is concomitant with accumulation of free radicals (PandiPerumal et al 2013), oxidative stress increases when exposed to EMF, hence supplementation of antioxidants were recommended under these conditions (Zwirska-Korczala et al 2004;Sokolovic et al 2008;El-Helaly and Abu-Hashem 2010;Kerman and Senol 2012). Interestingly, the EMF was not only reported to increase the life span of free radicals (Kabuto et al 2001;Stevens 2004), but was also involved in weakening the antioxidant defense mechanism (Lee et al 2004;Falone et al 2008), leading to increased oxidative stress condition (Blank and Goodman 2009;Martinez-Samano et al 2012). Several earlier studies have suggested that short and long-term exposure to 40-60 Hz ELF magnetic fields (MF) induce oxidative stress on various regions of the rodent's brain such as, cerebellum, hippocampus and striatum (Fu.…”
Section: Introductionmentioning
confidence: 99%
“…The Non-thermal effect due to normal cellular use causes temperature increment and hence metabolic cell stress but is compensated by thermo receptor molecules containing stress proteins in cells to protect from heat shock [7] . As the stress proteins occurs for both ELF and RF, having different energy levels [8] are unaffected by thermal effects. It has various symptoms like burning sensations in the skin of the head, headaches, dizziness, fatigue, disturbances to sleep and digestive systems, loss of mental attention to react and memory retentiveness [9] .…”
mentioning
confidence: 99%